Functional nerve cuff electrode with controllable anti-inflammatory drug loading and release by biodegradable nanofibers and hydrogel deposition - Park, Sung Jin; Lee, Yi Jae; Heo, Dong Nyoung; Kwon, Il Keun; Yun, Kwang-Seok; Kang, Ji Yoon; Lee, Soo Hyun (ELSEVIER SCIENCE SA, 2015)
This paper demonstrates a polyimide nerve cuff electrode with a controllable drug loading/release function for stable recording of peripheral nerve signals and stimulation and minimizing inflammation. For control of anti-inflammatory drug loading/release, dexamethasone (DEX)-loaded poly L-lactic acid (PLLA) and/or poly lactic-co-glycol acid (PLGA) nanofibers were deposited on a functional nerve cuff electrode by the electro-spinning method, which can control the weight of DEX loading on the functional nerve cuff electrode. Then, UV patternable polyethylene glycol (PEG) was coated on the functional nerve cuff with DEX-loaded nanofibers for the acceleration of the release rate of the drug. Through high performance liquid chromatography (HPLC), DEX release rates were increased from 16 to 28% (PLLA-loaded nanofibers) and from 68 to 87% (PLGA-loaded nanofibers) due to the increased diffusion rate of DEX after 28 days, respectively. In addition, the functional nerve cuff electrode was electro-polymerized with poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) as a conductive polymer in order to recover the decreased electrical properties caused by PEG patterning. The impedance measured at 1 kHz was 342 Omega mm(2), which was extremely lower than the value of 1046 Omega mm(2) of PEG-patterned cuff electrodes. Through the acute ex-vivo test of SD rat's sciatic nerve, the functional nerve cuff electrode with PEDOT:PSS exhibited stable and effective recording of the nerve's signals despite PEG patterning. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: BRAIN-MACHINE INTERFACES; ELECTRICAL-STIMULATION; DEXAMETHASONE; CONDUCTIVITY; DELIVERY; SYSTEM; CORTICOSTEROIDS; NEUROPROSTHESES; MORPHOLOGY; POLYMERS